Principal Strategies in Improving Information and Communication Technology Competence in Teachers - Yusmiati Yusmiati; Minnah El Widdah; Abdullah Yunus (Journal of Educational Management Research, 2025)
Developing teachers’ information and communication technology (ICT) competence requires strategic leadership at the school level. This study explores the principal’s strategies for enhancing ICT competence among rural public junior high school teachers. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation at school. The findings reveal that most teachers demonstrate basic to intermediate ICT skills, with tools such as PowerPoint and LCD projectors being the most common. Supporting factors include the availability of ICT facilities, regular training, strong principal leadership, peer collaboration, and partnerships with the Education Office. However, limited funding, unstable internet, low teacher confidence, and heavy workloads hinder progress. The principal’s strategic responses include organizing training programs, involving teachers in external technical guidance, optimizing existing ICT tools, promoting peer learning through MGMP forums, and providing recognition to innovative teachers. This study contributes to the discourse on digital leadership and teacher capacity-building in resource-constrained contexts.